2005
DOI: 10.1037/0033-3204.42.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an alliance-focused treatment for personality disorders.

Abstract: This paper presents a study with the aim of evaluating the relative efficacy of an alliance-focused treatment, brief relational therapy, in comparison to a short-term dynamic therapy and a cognitive-behavioral therapy on a sample of highly comorbid personality disordered patients. Results indicated that the three treatments were equally effective on standard statistical analyses of change, including those conducted on repeated measures and residual gain scores. Some significant differences were indicated regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 49 publications
5
120
0
6
Order By: Relevance
“…The fact that Axis II patients started therapy with lower WAI scores and higher confrontation and withdrawal scores is consistent with previous theoretical and empirical evidence showing that there is a high likelihood of ruptures with such clients (Benjamin & Karpiak, 2001;Muran, Segal, Samstag, & Crawford, 1994), and personality disordered patients benefit the most from therapeutic interventions focused on alliance negotiation (Muran, Safran, Samstag, & Winston, 2005). In a qualitative study in which we explored the experience of rupture episodes of therapists and their patients with personality disorders we found that unresolved ruptures had a strong negative impact on the alliance and on the client.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The fact that Axis II patients started therapy with lower WAI scores and higher confrontation and withdrawal scores is consistent with previous theoretical and empirical evidence showing that there is a high likelihood of ruptures with such clients (Benjamin & Karpiak, 2001;Muran, Segal, Samstag, & Crawford, 1994), and personality disordered patients benefit the most from therapeutic interventions focused on alliance negotiation (Muran, Safran, Samstag, & Winston, 2005). In a qualitative study in which we explored the experience of rupture episodes of therapists and their patients with personality disorders we found that unresolved ruptures had a strong negative impact on the alliance and on the client.…”
Section: Discussionsupporting
confidence: 71%
“…Tryon and Kane (1995) also found that weakened alliances were associated with dropped cases. In addition, Muran, Safran, Samstag, and Winston (2005) found that patients in brief relational therapy (BRT), which focuses on the repair of alliance ruptures, had significantly lower dropout rates as compared to patients who received CBT. It is important to note that because we did not evaluate therapist interventions or therapist contributions to detected ruptures, we cannot confirm this possibility that the therapists were unable to resolve ruptures in unsuccessful and dropped cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Através de um rastreamento do número de sessões utilizado em pesquisas de tratamentos psicodinâmicos de curta duração realizadas a partir do ano 2000 [28][29][30][31][32][33][34][35][36][37][38][39] e que apontam um amplo espectro de uma a 63 sessões, foi possível chegar ao número mínimo de 18 sessões, e cinco pacientes foram incluídos com essa freqüência.…”
Section: Pacientesunclassified
“…Few of these studies included measures assessing core PD pathology. For example, interpersonal problems, often considered a major aspect of PD pathology, were assessed in only two psychodynamic studies (Bateman & Fonagy, 2001Muran, Safran, Samstag, & Winston, 2005). Furthermore, measures theoretically relevant to the goals of psychodynamic psychotherapy (e.g., reflective functioning and levels or forms of attachment) have surprisingly rarely been used (for an exception see Levy et al, 2006).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%